(untitled) (Journal of actual problems of jurisprudence, 2020)
Given article analyses the causes of increasing problems of shared water use by transboundary rivers in Central Asia. The existing complex problems of relations between the states of the region reduce the effectiveness of individual states, the work of industries, the level of life safety, the existence of water and terrestrial ecosystems. Water use in the region and the ability to control it is turning into a powerful mechanism of economic and political pressure from some states of the Central Asian region. According to the fact that on a number of issues the governments of Central Asia cannot come to a consensus, it is proposed to use the experience of Europe. It is noted that in spite of the development of contractual international water legislation, issues of joint water use are exacerbated in practice and develop into international conflicts. In order to avoid conflicts, the author believes that despite the active position of Kazakhstan in international politics and the quantity and quality of agreements concluded by him on the use of transboundary opening facilities, one should consider options for using own facilities and reduce the consumption of transboundary rivers. It is also proposed to continue the policy of hydro-diplomacy based on economical and environmentally friendly water use. Key words: water law, water security, transboundary water bodies, shared water use, legal regulation.